Human Disabled-2 regulates thromboxane A2 signaling for efficient hemostasis in thrombocytopenia - Hui-Ju Tsai; Ya-Fang Chang; Ya-Ju Hsieh; Jiaan-Der Wang; Chih-Ching Wu; Meng-Ying Ho; Ju-Chien Cheng; Ding-Ping Chen; Hsiang-Rui Liao; Ching-Ping Tseng (Nature Communications)
Abstract Understanding platelet protein functions facilitates better assessment of platelet disorders. Megakaryocyte lineage-restricted human Disabled-2 knock-in (hDAB2-KI) mice are generated to delineate the functions of hDab2, a regulator of platelet function, in the control of bleeding associated with thrombocytopenia. Here we show that hDab2-KI mice with thrombocytopenia display decreased bleeding time when compared to the control mice. hDab2 augments thromboxane A2 (TxA2) mimetic U46619- but not other agonists-stimulated granule secretion, integrin activation, and aggregation at a lower platelet concentration in vitro. Binding of hDab2 to phosphatidic acid (PA) facilitates formation of the PA-hDab2-AKT complex leading to an increase in U46619-stimulated AKT-Ser473 phosphorylation and the first wave of ADP/ATP release. Consistent with these findings, hDab2 expression in platelets from patients with immune thrombocytopenic purpura is positively correlated with U46619-stimulated ATP release, which in turn inversely correlated with their bleeding tendency. hDab2 appears crucial in regulating bleeding severity associated with thrombocytopenia by a functional interplay with ADP/ATP release underlying TxA2 signaling.